CREATION OF HIGHLY EFFECTIVE X-RAY SOURCES USING NANOMATERIALS - Olimjonova Go’zal Olimjon qizi (Scholar Express Journals, 2023)
Nanomaterials and nanotechnologies are one of the priorities of the development of modern materials science. Due to the fact that it is necessary to produce devices that can prevent and reduce the negative effects of X-rays on the human body, nanomaterials are thoroughly studying and X-ray devices are created using effective methods of devices. The main components nanotechnology of this science are nanomaterials, we study its components and relevance
Keywords: Nanofocus; Microfocus; X-Ray Tubes